Adoption of audit technology in audit firms - Rosli, Khairina; Paul, H.P. Yeow; Siew, Eu-Gene (2013)
This paper investigates audit technology adoption based on Technology-Organization-Environment (TOE) framework, Diffusion of Innovation and Institutional theories.As more audit firm’s clients use enterprise information systems, it is important for audit firms to adopt audit technologies in auditing.Descriptive statistics results from questionnaire survey on 38 audit firms’ auditors reveal that more than 50% of auditors had never used computer-assisted-audit tools other than electronic spreadsheets.Despite the low adoption, the respondents agreed that audit technology is cost-effective.Low mean ratings were given on other indicators of audit technology adoption i.e. technology compatibility, technology complexity, organization readiness, top management support, employee’s competency, client’s system complexity, competitive pressure, vendors’ and professional accounting bodies’ supports. Results also show that firm size influenced the adoption level.Theoretically, this paper contributes in developing a comprehensive audit technology adoption framework by incorporating client’s system complexity and professional accounting body support that enhances the original TOE framework